Anti-diabetic potentials of Clerodendrum inerme, Jasminum mesyni Hance and Callistemon citrinus on nicotinamide-streptozotocin induced type 2 diabetic rats - Bharat Bhushan; Satish Sardana; Gulshan Bansal (International Journal of Phytomedicine, 2015)
To investigate antidiabetic potential of alcoholic leaves extract of Clerodendrum inerme, Jasminum mesyni Hance and Callistemon citrinus on nicotinamide-streptozotocin induced type 2 diabetic rats The comparative antidiabetic activity was conducted in NAD+STZ wistar rats of either sex. The leaves extracts of C. inerme, J. mesyni Hance and C. citrinus were administered at a dose of 400 and 600mg/kg p.o. for 4 Weeks and observed for antidiabetic study. During 28 days of treatment, rats were observed weekly for hypoglycaemic activity. The glucose level of all groups were determined after 0, 7, 14, 21 days. The blood samples for glucose estimation were withdrawn by retro-orbital plexus puncture method for antidiabetic activity. All the plant extracts lowered the blood glucose level after 21 days significantly with respect to the diabetic control. However, only ethanolic extract of C. inerme at 400mg/kg p.o. exhibited maximum reduction of blood glucose level as compared to the J. mesyni Hance and C. citrinus. The results demonstrated that C. inerme has potent antidiabetic effect as compared to extracts of another two plants.